Urban trees and stormwater runoff: the role of rainfall partitioning and transpiration on water regulation at the tree and watershed scales - Nooraei Beidokhti, Alireza (Kansas State University, 2020)
Trees provide a variety of ecosystem services to urban communities. In addition to regulating urban microclimate and air quality, providing wildlife habitat, and improving the sense of well-being for people, trees also play a role in regulating the urban hydrologic cycle and thus contribute to the stormwater management. However, the actual effectiveness of preserving or planting trees and the extent to which urban tree systems (which include individual trees to remnant forests located in urban landscapes) contribute to the reduction of runoff volume at various scales is still unclear. This dissertation aimed to answer the overarching question of the extent to which urban tree systems are an effective and scalable approach for regulating the hydrologic response of urban watersheds. To address the question, (1) a meta-data analysis of the existing field studies was conducted to examine the magnitude and drivers of precipitation partitioning and transpiration processes by urban trees, taking into account tree structural characteristics and climatic conditions, at a tree scale, and (2) a mechanistic urban forestry hydrologic model was developed for three study watersheds in the Kansas City metro area, to better clarify the role of urban trees on the reduction of runoff at a watershed scale. At the tree-scale, the results of this analysis indicated that individual urban trees can intercept 10% to 60% of annual precipitation. In addition, the sap flux for studied urban trees ranged from 13.08 to 464.15 g/cm²/day At the watershed-scale, increasing tree canopy cover from 25% to 100% was predicted to reduce stormwater runoff volume from 6 to 38% for a relatively frequent storm event (25 mm over 24 hours); however, an attendant reduction in an impervious surface area representative of replacing existing impervious surfaces with tree planting pits was required to achieve these volume reductions. By systematically analyzing empirical evidence as well as a modeling approach regarding the potential effectiveness of urban tree systems, this work could shed some more light on how urban tree systems can be accounted for in stormwater regulatory and management frameworks.
Keywords: Precipitation; Throughfall; Meta analysis; Watershed modeling; Runoff management